Household decision-making for everyday travel : a case study of walking and cycling in Lancaster (UK) - Pooley, C; Horton, D; Scheldeman, G; Tight, M; Jones, T; Chisholm, A; Harwatt, H; Jopson, A (Elsevier, 2011)
Increased walking and cycling for short journeys in urban areas has many obvious advantages yet so far gains from the promotion of more sustainable travel of this type are mostly small. This paper reports on a large research project which uses a mixed method approach to explore attitudes to and perceptions of walking and cycling and which examines the process of household decision-making for everyday travel and the constraints that this imposes. Using survey, interview and ethnographic data it is argued that many people hold ambiguous and sometimes contradictory views of walking and cycling as effective means of everyday travel, that what they do rarely matches precisely what they believe and that the complexity and contingency associated with everyday travel for many households is a major barrier to the use of more sustainable travel modes. It is suggested that better understanding of these processes could help to inform both future transport policy and the promotion of walking and cycling for short trips in urban areas.